2008
DOI: 10.1097/01.prs.0000304469.81239.f0
|View full text |Cite
|
Sign up to set email alerts
|

Lower Blepharoplasty with Capsulopalpebral Fascia Hernia Repair for Palpebral Bags: A Long-Term Prospective Study

Abstract: At long-term follow-up, fat-preserving capsulopalpebral fascia repair for palpebral bags demonstrates superiority to standard blepharoplasty with lipectomy, with significantly lower recurrence of palpebral bags. In a small percentage of patients undergoing capsulopalpebral fascia hernia repair, limited fat resection in selected patients may eliminate hernia recurrence.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
14
0
3

Year Published

2010
2010
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(19 citation statements)
references
References 15 publications
2
14
0
3
Order By: Relevance
“…The fat-preserving blepharoplasty associated with periorbital fat mobilization would be addressed to a specific group of patients who demonstrate the tear trough triad, while for most patients the traditional procedure would be appropriated, but the most important consideration is that additional elements would be added to the operative plan based on individual patient analysis. When the total operative times between the two surgical groups were compared, the authors found them comparable, as noted by Parsa [21].…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…The fat-preserving blepharoplasty associated with periorbital fat mobilization would be addressed to a specific group of patients who demonstrate the tear trough triad, while for most patients the traditional procedure would be appropriated, but the most important consideration is that additional elements would be added to the operative plan based on individual patient analysis. When the total operative times between the two surgical groups were compared, the authors found them comparable, as noted by Parsa [21].…”
Section: Discussionmentioning
confidence: 93%
“…The evolution of this procedure has resulted in divergent concepts. Some authors favor the maintenance of the fat bags, others are against touching the orbicularis oculi muscle, and still others recommend muscle cutaneous flaps and ample undermining of the orbicularis oculi muscle [2,4,12,[14][15][16][17][18][19][20][21].…”
Section: Discussionmentioning
confidence: 99%
“…Quando se opta por realizar a blefaroplastia com preservação e mobilização das bolsas adiposas, presume-se que o volume destas bolsas não estejam aumentados, sendo sua preservação importante para a manutenção da jovialidade da projeção do globo ocular em relação a face (8,9,16,19) . Quando os autores compararam o tempo de cirurgia entre os dois grupos, observou-se que não houve diferença estatisticamente significante entre eles (26) . Durante a análise das fotografias observou-se que a maioria dos pacientes tinha flacidez cutânea (74%), bolsas adiposas na pálpebra inferior (76%) e deformidade denominada de sulco nasojugal pronunciado ("tear trough") (74%).…”
Section: Discussionunclassified
“…46,47 Although immediate results of these techniques may appear acceptable, they do not improve the vertical height of the lower lid and therefore aesthetic improvement is not durable. 6,10,31,43,[56][57][58][59][60][61][62][63][64] The second MOC-PS blepharoplasty article used an evidence-based approach to review many of these articles, many of which discussed newer approaches, whereas others provided support for more traditional techniques. 21,25 Although continued use of a skin pinch technique is necessary in situations of excess skin, 48 recent discussions of lower blepharoplasty have focused more on preservation and repositioning rather than removal of tissue.…”
Section: Lower Lid Blepharoplastymentioning
confidence: 99%